Breaking Barriers: Investigating Recruitment, Workplace Culture, and Career Progression Factors Affecting Underrepresented Groups in Maritime Deck Officer and Port Operations Roles (International Journal of Economics Management and Social Science, 2026)
A well-...........  Maritime deck officer and port operations roles remain male-dominated professions with persistent underrepresentation of women and other marginalized groups, despite global human capital shortages and evidence that diversity enhances organizational performance. This mixed-methods study examined barriers to recruitment and retention of women and underrepresented groups in maritime technical roles through interviews with 86 participants (women in maritime roles, male colleagues, employers, educators, industry recruiters) and surveys with 523 maritime employees across deck operations, port management, and maritime education contexts. Qualitative findings identified multi-level barriers: institutional (limited dedicated recruitment targeting women, insufficient awareness of maritime career opportunities among female secondary students), workplace culture (masculinized language and norms, sexual harassment incidents, limited mentorship), family structure (difficulty combining maritime careers with family responsibilities), and career progression (glass ceiling effects limiting advancement, gender-based pay inequities). Quantitative analysis (Cronbach's α=0.81 for workplace culture scale) revealed that women reported significantly lower workplace climate perceptions (mean 2.8/5.0 versus male mean 4.1/5.0, t(521)=-12.3, p